Gaya Mengajar Guru dalam Meningkatkan Hasil Belajar Kognitif pada Mata Pelajaran Fiqih Kelas II Madrasah Ibtidaiyah - Dwi Rohmawati; Rofiatun Nisa; Hasyim Hasyim (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2023)
The aims of this research are to: analyze the teacher's teaching style in the Fiqh subject; find out the efforts of teachers of fiqh subjects in improving cognitive learning outcomes. This type of research is a qualitative descriptive approach. Data collection methods in this study were interviews, observation, and documentation. The author's data analysis technique uses data reduction, data presentation, and conclusions/verification. Meanwhile, the author's data validity test uses source triangulation. The results of this study indicate that the teaching style of teachers at the MI Nurul Khoiriyah Siwuran school is quite good and effective. Because what is implemented by teachers in schools is to use the teacher's style and character that attracts students' atention. Teachers also have a critical role in teaching. A teacher does not only know about the material to be taught. However, it must have a solid personality to make it a student role model. Teachers must also train skills, attitudes, and mentality to inspire students and become role models so that students can feel comfortable when explained by the teacher. Teachers can create a new atmosphere by using varied teaching styles, such as image media, video images, and study groups to discuss the learning material. And based on the results of the study, it was found that efforts to improve cognitive learning outcomes are of them by creating a new atmosphere, a comfortable atmosphere for learning in the classroom, and using a variety of effective teaching styles so that they understand without them.